High rates of JCV seroconversion in a large international cohort of natalizumab-treated patients. (April 2021) - Dwyer, Christopher M.; Jokubaitis, Vilija G.; Stankovich, Jim; Baker, Josephine; Haartsen, Jodi; Butzkueven, Helmut; Cartwright, Adriana; Shuey, Neil; Fragoso, Yara Dadalti; Rath, Louise; Skibina, Olga; Fryer, Kylie; et al.
Aims: To retrospectively assess factors associated with John Cunningham virus (JCV) seroconversion in natalizumab-treated patients. Background: Natalizumab is highly effective for the treatment of relapsing–remitting multiple sclerosis (RRMS), but its use is complicated by opportunistic JCV infection. This virus can result in progressive multifocal leukoencephalopathy (PML). Serial assessment of JCV serostatus is mandated during natalizumab treatment. Methods: Patients treated with natalizumab for RRMS at six tertiary hospitals in Melbourne, Australia ( n  = 865) and 11 MS treatment centres in Brazil ( n  = 136) were assessed for change in JCV serostatus, duration of exposure to natalizumab and prior immunosuppression. Sensitivity analyses examined whether sex, age, tertiary centre, prior immunosuppression or number of JCV tests affected time to seroconversion. Results: From a cohort of 1001 natalizumab-treated patients, durable positive seroconversion was observed in 83 of 345 initially JCV negative patients (24.1%; 7.3% per year). Conversely, 16 of 165 initially JCV positive patients experienced durable negative seroconversion (9.7%; 3.8% per year). Forty patients (3.9%) had fluctuating serostatus. Time-to-event analysis did not identify a relationship between JCV seroconversion and duration of natalizumab exposure. Prior exposure to immunosuppression was not associated with an increased hazard of positive JCV seroconversion. Male sex was associated with increased JCV seroconversion risk [adjusted hazard ratio 2.09 (95% confidence interval 1.17–3.71) p  = 0.012]. Conclusion: In this large international cohort of natalizumab-treated patients we observed an annual durable positive seroconversion rate of 7.3%. This rate exceeds that noted in registration and post-marketing studies for natalizumab. This rate also greatly exceeds that predicted by epidemiological studies of JCV seroconversion in healthy populations. Taken together, our findings support emerging evidence that natalizumab causes off-target immune changes that may be trophic for JCV seroconversion. In addition, male sex may be associated with increased positive JCV seroconversion.